HUBUNGAN MOTIVASI INTRINSIK DAN EKSTRINSIK ORANG TUA DENGAN TINDAKAN MENYEKOLAHKAN ANAK DI MI AL-MA’ARIF 02 SINGOSARI - Mulyoto, Galih Puji; Setiawan, Moch Rizki (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2023)
This study aims to describe the factors that cause parents to be motivated to send their children to MI Al-Ma'arif 02 Singosari. This study also aims to determine the dominant factor of parents being motivated to send their children to MI Al-Ma'arif 02 Singosari. This study uses a quantitative approach to the type of survey research. The subjects of this study were all parents of second grade students of MI Al-Ma'arif 02 Singosari as many as 75 people. Data collection techniques using questionnaires, interviews and documentation.The results showed that the factors that caused parents to be motivated to send their children to MI Al-Ma'arif 02 Singosari consisted of intrinsic and extrinsic motivation. Intrinsic motivation factors include: (1) understanding Islamic religious science (2) understanding the Koran (3) understanding fiqh (4) having noble character and (5) achievement. While the extrinsic motivation factors include: (1) School Environment (2) Infrastructure (3) Vision and Mission (4) Quality of Religious Education (5) Educator Profile (6) Curriculum (7) Activities in School (8) Governance Orderly (9) Extracurricular (10) Cost (11) Family Environment (12) Social Environment. The dominant factor of parents' intrinsic motivation is an indicator of understanding fiqh and the dominant factor of parents' extrinsic motivation is an indicator of school activities.